Повторное продление эксплуатации роторов высокого и среднего давления турбины К-200-130 Кураховской ТЭС - Черноусенко, Ольга Юрьевна; Рындюк, Дмитрий Викторович; Пешко, Виталий Анатольевич (НТУ "ХПИ", 2018)
Энергоблоки ДТЭК «Кураховская ТЭС» мощностью 200 МВт с паровыми турбинами К-200-130 после достижения ими паркового ресурса на сегодняшний день требуют принятия решения о возможности их дальнейшей эксплуатации. Проведена оценка остаточного ресурса на базе 3D- пространственных аналогов для РВД и РСД паровой турбины К-200-130 мощностью 200 МВт блоков № 4, 5 ДТЭК «Кураховская ТЭС» с экспериментально полученными коэффициентами запаса прочности металла с учетом реальных условий эксплуатации согласно станционных данных поврежденности. Представлены рекомендации по повторному продлению срока эксплуатации высокотемпературного энергетического оборудования.

The power-generating units at the Kurakhovska Heat Power Plant of 200MW with steam turbines K-200-130 that reached their fleet life require today the decision taking on the possibility of their further operation. In this connection, the problems of taking into consideration the damages caused by the action of high local temperatures, the local temperature nonuniformity and a reliable estimation of the residual life of rotors is vital. Based on the developed methods of calculated estimate of the action of local nonuniformity of heat losses we computed the residual life of HP and AP rotors of the steam turbine K-200-130-3. The elastically deformed rotor state was calculated taking into account the joint action of the temperature gradient, centrifugal forces and steam-pressure in operation. A total level of damage of the metal of HPR and APR was defined based on the computations of the low-cycle fatigue and the static damageability. The recommendations were given on the opportunity for the refreshing extension of the service life of high pressure rotors and low pressure rotors of the steam turbine of 200 MW used for the power-generating units No 4 and No 5 at Kurakhovska heat power plant, exceeding their fleet life stated in current normative documents. High pressure rotors and low-pressure rotors of the power-generating unit No 4 at Kurakhovska heat power plant can operate for additional 45 thousand hours and the power-generating unit No 5 can additionally operate during 50 thousand hours.
Refreshing extension of the operation of high pressure rotors and average pressure rotors of the turbine K-200-130 at the Kurakhovska heat power plant
Keywords: ротор; давление среднее; давление высокое; пуск холодный; ресурс остаточный; усталость малоцикловая; прочность; rotor; average pressure; high pressure; cold start-up; residual life; low-cycle fatigue; strength